Teleworking: myths and realities - Arias Oliva, Mario (2011)
In the next few years we will find enormous differences in many aspects of our lives. Old concepts will need to be revised and new ones will need to be defined. We need to find a new concept of work, a new definition of what work is in the information society, and what it should be. We must determine the full implications of this new concept of working and analyze its impact on society, organizations and individuals. In this new conception of work, teleworking is becoming increasingly more important. It is having important effects on society, individuals and organizations. New forms of working are emerging, and these have the logical consequences on individuals, organizations and society. Teleworking will bring many positive aspects, create new opportunities and offer new advantages to workers, firms and communities. But it could also bring many negative aspects and create new problems.